Mediterranean Honor and Beyond. The Social Management of Reputation in the Public Sphere - Giordano, Christian (Sociologija. Mintis ir veiksmas, 2005)
This article aims at reconstructing the logic of honor by analyzing the classic example of Mediterranean societies, which on several occasions have been labeled, rightly or wrongly, “honor and shame societies”. Consequently, we will show that honor strengthens the hierarchic order and class structure of these societies. And, far more important, we will highlight that honor is not so much a moral code as rather a language and set of rational social strategies whose purpose is the skilful management of one’s individual and group reputation by trying to avoid being publicly discredited and humiliated. The struggle for recognition is thus strictly linked to the strenuous defense of one’s mask and façade, both against the constant threats of enemies and rivals acting in the arenas of public opinion. The final part of this article will show how these characteristics of Mediterranean honor – too hurriedly written off as archaic, obsolete, and dying out – can paradoxically be detected in modern societies’ management of reputation. The logic of honor will thus be presented as a transcultural phenomenon that goes beyond the historical context as well as the ethnographic and geographical ones.